2021
DOI: 10.30538/psrp-easl2021.0066
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative analysis of a mathematical model of divorce epidemic with anti-divorce therapy

Abstract: Marriage is the living together of two persons as husband and wife. Separation and Divorce are the frontier challenges facing the existence of stable family system. In this paper, we construct an epidemiological model of divorce epidemic using standard incidence function as force of marital disunity. The study examines qualitatively that the two equilibra (divorce-free and endemic equilibrium point) are globally stable by Lyapunov functions. Numerical results reveal that, anti-divorce protocols and reconciliat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In their study, they concluded that increasing the number of marriages that go into separation and educating them along with reducing contact with infectious divorcees help in combating the divorce epidemic. A study on qualitative analysis of a mathematical model of divorce epidemic with anti-divorce therapy was propounded by [13], they found out that anti-divorce protocols and reconciliation can jointly stabilize marriages. Bifurcation analysis of mathematical model analysis of marriage divorce [21] was performed with the conclusion that divorce has eaten deep into the fiber of the society.…”
Section: Introductionmentioning
confidence: 99%
“…In their study, they concluded that increasing the number of marriages that go into separation and educating them along with reducing contact with infectious divorcees help in combating the divorce epidemic. A study on qualitative analysis of a mathematical model of divorce epidemic with anti-divorce therapy was propounded by [13], they found out that anti-divorce protocols and reconciliation can jointly stabilize marriages. Bifurcation analysis of mathematical model analysis of marriage divorce [21] was performed with the conclusion that divorce has eaten deep into the fiber of the society.…”
Section: Introductionmentioning
confidence: 99%